Belajar Matematika dalam Perspektif Islam - Imamuddin, M.; Isnaniah, Isnaniah; Januar, Januar; Hadini, Hadini; Andryadi, Andryadi; M., Zaharuddin; Susanti, Weti (Kaunia: Integration and Interconnection Islam and Science Journal, 2025)
This study examines the importance of learning mathematics from an Islamic perspective, arguing that this discipline is not only a cognitive tool, but also a spiritual means of understanding the greatness of Allah SWT. In Islam, mathematics has a unique position as the Qur’an implicitly refers to order, balance and careful calculation in the creation of the universe, as seen in the movement of celestial bodies or the division of inheritance. Hadiths of the Prophet Muhammad also encourage the pursuit of knowledge and the use of reason, which broadly includes the study of mathematics as a foundation for the advancement of science. Through the library research method, the researcher collected and analyzed various literature sources, including journal articles, academic books, books of tafsir, and Hadith, both in digital and print formats. To ensure validity and depth of analysis, the researcher applied data triangulation, comparing and confirming findings from various sources. The results of the analysis show that learning mathematics can foster tafakur (contemplation) and tadabbur (deep appreciation) of Allah’s creation, thus increasing faith and piety. The study concludes that mathematics, from an Islamic perspective, is a way to uncover the secrets of the universe and witness the signs of divine power, making it a worshipful activity with a spiritual dimension.